The Effect of Speech Disfluency on English Speaking Performance among Third-Semester Students: Manuscript Submission: Speech Disfluency in EFL Speaking Performance - Nur Shiyam Mendrofa; Siti Khafifah Shaleh N.Cui; Oktoberlianus Zendrato (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study investigates the effect of speech disfluency on English speaking performance among third-semester students of the English Education Study Program at Universitas Nias. Grounded in psycholinguistic perspectives, speech disfluency is viewed as a natural outcome of cognitive processing during speech production, particularly in a second language context. A quantitative descriptive research design was employed, involving ten students selected through purposive sampling. Data were collected through audio-recorded English self-introduction tasks and transcribed for analysis. The analysis focused on identifying and quantifying common disfluency features, including fillers, repetitions, and pauses. The findings reveal that speech disfluency frequently occurs in students’ spoken English and is closely associated with difficulties in speech planning and lexical retrieval. Rather than indicating communicative failure, these disfluencies reflect ongoing language development among EFL learners. The study highlights the importance of considering speech disfluency as an informative aspect of speaking performance evaluation in higher education EFL contexts.